Decentralized Solutions for Intellectual Property Security Using the InterPlanetary File System - Shofiyul Millah; Andri Waskito; Ester Ananda Natalia; Lase, Steven Harazaki; Marta Rodriguez (Blockchain Frontier Technology, 2025)
In the digital era, protecting intellectual property rights (IPR) presents major challenges due to the vulnerabilities of centralized storage systems, which are susceptible to data breaches, manipulation, and unauthorized access. This study explores the adoption of the InterPlanetary File System (IPFS) as a decentralized alternative for securing IPR, with a focus on user-centric factors that are often neglected in prior research. Specifically, the research examines how five key constructs security, transparency, persistence, ease of use, and cost efficiency influence adoption decisions among non-technical users. A quantitative method was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data collected from 110 digital business students. The findings reveal that all five constructs significantly impact users’ willingness to adopt IPFS. This is supported by strong outer loading values (>0.70), high Average Variance Extracted (AVE >0.50), and high reliability scores (Cronbach’s alpha and composite reliability >0.70). These results validate the proposed adoption model and underscore the importance of behavioral and perceptual considerations in decentralized technology acceptance. Furthermore, the study highlights the relevance of integrating IPFS in academic and SME environments, aligning with Sustainable Development Goals (SDG 4, 9, and 16) by promoting secure, inclusive, and innovative digital infrastructure. Future studies are encouraged to include more diverse demographic groups and address regulatory and interoperability challenges to enhance scalability and adoption.